Emerging ecological risks in asian agricultural development and food security - Kada, Ryohei (2010)
In the course of rapid economic development and agricultural development, many Asian countries have increased agricultural and food production, which has led to the extensive degradation of natural resources of ecosystem services. More specifically, the adoption of modern technology such as intensive agricultural chemical use and shift toward monoculture has resulted in serious soil and water degradation. This paper examines the current issues of sustainability of agriculture, forestry, and fisheries in Asia in relation to ecological risks (i.e., reduction in ecosystem services). This is mainly due to the fact that adoption of more advanced technologies and increased rate of cultivation of marginal lands generally tend to decrease the sustainability of agriculture and fisheries. On the other hand, the continuous outmigration of rural population into megacities has caused social unrest in metropolitan areas with the abandonment of agricultural and rural resources and has led to the loss of active labor force and the emergence of an aging structure. This is the so-called vicious circle of poverty and resource degradation. Such unsustainable patterns of development gradually imperil biodiversity and ecosystem services, which are crucially important in South and Southeast Asia. The basic issues here are: 1) whether Asian agriculture and fisheries can stably supply the sufficient amount and quality of food needed to meet the demands of a rapidly growing population; and 2) how this can be done without jeopardizing the natural and environmental resources. In this paper, the author examines the influences brought about by continued agricultural growth in Asia, especially on biodiversity and other ecological services. The outcomes of recent agriculturaldevelopment will be evaluated to come up with policy alternatives compatible with ecological goals. Policy implications of such ecological influences onfood security in Asia will also be examined.
Keywords: Agricultural development; Food security; Natural resources